Improvements in billing processes and information systems increase cash collections in a public health care system. - Steele A; Eisert S; Gabow P (Health Care Manager, 2001)
Management information systems are an essential tool for health care managers. Denver Health, an integrated safety net institution, upgraded its financial management information system during 1997 and experienced almost an 18 percent or $23 million increase in cash collections from 1997 to 1998 and a 17 percent or over $25 million increase from 1998 to 1999. Cash collections continued to increase in 2000 with a $12.0 million (6.8%) ncrease over 1999. This article explains the information system factors that have contributed to this increase and describes the continued management efforts that are expected to continue to improve cash collections. Copyright © 2001 by Aspen Publishers, Inc.